Labor market integration of asylum seekers in Europe: Recent trends and barriers - Martin Lange; Sarah McNamara; Philipp Schmidt (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
The labor market integration of asylum seekers remains a contested issue. Using the EU-Labor-Force-Survey, we characterize the state of asylum seekers' labor market integration in Europe, and provide representative statistics on several dimensions of integration. We compare asylum seekers to natives and economic migrants and find that asylum seekers struggle to integrate across European states, exhibiting employment rates of 10 percentage points lower than that of natives, on average, as well as a notable gap in job-quality. Analyzing self-reported barriers to employment, we document that asylum seekers' lower employment rates and job-quality are likely the result of institutional hurdles.
Keywords: F22; K37; J11; 330; asylum seekers; refugees; labor market integration